CHANGING MASCULINITIES IN CRIME FICTION - DEVAKI S,; Meenu B, (International Journal of Psychosocial Rehabilitation, 2020)
Crime fiction has always been hailed for being accommodative of revisionist structures and as a powerful tool in combating gender stereotypes. Crime solving and sleuthing is popular on television dramas as well, some of these shows being on TV for more than a decade, for example, Criminal Minds on CBS or ITV’s Agatha Christie’s Poirot. With the abundance of content available on small screens, be it television, or through streaming platforms such as Netflix, it is safe to assume that there has never been a better time to study the impact of these on-screen portrayals of gender, its complexities and stereotypes as well. This paper examines the depiction of masculinity in some of the recent popular crime dramas. It considers if the feminist movement and its deconstruction of gendered identity had any impact on these onscreen portrayals of male detectives. As MacKinnon (2003) suggests the police and crime drama can be presumed as one of the most masculine of television genres because it tends to focus on the public sphere, professional roles and the male world of work. As masculinity itself is being re-defined to fit in a modern context, this paper investigates the ways in which these male centered narratives negotiate the struggles of their lead characters to fit on the spectrum and challenge the traditional masculine standards.